An empirical Investigation of the Nexus between Disclosure level and Financial Performance on Ethiopian Commercial Banks: A Simultaneous Equations Approach - Kefale, Degu; Malhotra, Keshav; Aggarwal, Monika (Gyan Management Journal, 2023)
The study aimed to examine the effect of disclosure on bank financial performance and the simultaneous relationship between them. To achieve the objective six-year secondary data was collected from seventeen Ethiopian commercial banks. To examine the effect of disclosure on financial performance and its simultaneous association with financial performance 3SLS (three-stage least square) regression was employed. The 3SLS estimation output indicated that financial disclosure has a significant effect on bank financial performance regardless of the proxies used to measure financial performance. Whereas social disclosure has a significant effect on return on equity and net interest margin. Regarding the simultaneous relationship between disclosure and financial performance; financial disclosure has a significant mutual association with all financial performance measures used in this study. However social disclosure level has a significant interdependent association only with net interest margin. From the estimation output bank managers can recommend that disclosure level and financial performance are interdependent variables that should be scrutinized to maximize their performance level.